The role of the IGF-1 Ec in myoskeletal system and osteosarcoma pathophysiology. (December 2016) - Armakolas, Nikolaos; Armakolas, Athanasios; Antonopoulos, Athanasios; Dimakakos, Andreas; Stathaki, Martha; Koutsilieris, Michael
Highlights: IGF-1 is very important in normal skeletal development and development of cancer. The IGF-1 system plays a crucial role in development and metastasis of osteosarcoma. The IGF-1 Ec peptide (PEc) is a key factor involved in cancer including osteosarcoma. PEc induces cellular proliferation and differentiation through an unknown receptor. PEc comprises an attractive target for the treatment of osteosarcoma, without affecting mature IGF-1. Abstract: Growth hormone (GH) regulated mainly liver-produced insulin-like growth factor 1 (IGF-1) is a key molecule in embryonic & post embryonic development that is also involved in cancer biology. Herein we review new insights of the role of igf-1 gene products and of the IGF-1Ec isoform in muscle and bone development/repair and its role in osteosarcoma pathophysiology, underlying the possible role of the Ec peptide as a future therapeutic target.